Analisis Pengukuran Tingkat Kepuasan Pengguna Terhadap Penerapan Aplikasi SISKEUDES Pada Kabupaten Banyuasin Sumatera Selatan - Mardiana Mardiana; Eka Hartati (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2019)
SISKEUDES is a village finance application that was developed in 2015 by the Financial and Development Supervisory Agency. Banyuasin District has implemented SISKEUDES, and in 2017 as many as 227 villages have used this system. The application of SISKEUDES with the level of user satisfaction can determine the success of the implementation of the SISKEUDES system itself. This study took a sample in Banyuasin district, South Sumatra province. The aim of the study analyzes the level of user satisfaction in the application of SISKEUDES using multiple linear regression. In this study, researchers used quantitative research methods with the application of the Green-Pearson model consisting of Easy of Use, Customization, Download Delay, and Content variables. This study uses a questionnaire measuring device consisting of 93 respondents from nineteen districts in Banyuasin district, where the measurement scale used is a Likert scale and data analysis is tested for validity, reliability and multiple regression. The results of the study get the regression equation Y = -0.4.727 + 0.1.050 X1 + 0.1.222 X2 + -0.082 X3 + 0.042 X4. The variables X1 and X2 significantly influence the variable Y, while the variables X3 and X4 have no effect on the variable Y.